From violent lone-actor types to lone-actor grievance-fueled violence: The Aarhus University shooting as an example of multi-facetted offender motivations and context-sensitive boundaries between violent lone-actor categories - Ebbrecht, Christopher Kehlet; Lindekilde, Lasse (Frontiers in Psychology, 2023)
Over the last decade, western societies have experienced an increase in acts of mass violence carried out by lone actors. While this concept is mostly associated with lone-actor terrorists, it also involves the actions of other single perpetrators, e.g., school shooters, workplace attackers, rampage shooters, and some forms of incel violence. In this article, we argue in favor of moving away from such categorization of violent lone-actor types and towards the unifying concept of lone-actor grievance-fueled violence. We illustrate the analytical benefits gained from such a conceptual shift by analyzing the Danish Aarhus University Shooting in 1994, where a single offender killed two students. While this attack is widely accepted as the only Danish school shooting in history, we identify signs of an extremist misogynist worldview held by what we today would call incels. This case serves as an illustration of the blurred and context-sensitive boundaries between violent lone-actor types and how nuances in offender motivation can be lost when lone-actor attacks are classified within a typological framework. Rather than simply recasting the Aarhus University Shooting as an incel attack considering the recent development of this category, we argue for the need to embrace the conceptualization of lone-actor grievance-fueled violence, which points towards the common genesis of lone-actor violence and allows for multi-faceted offender motivations. Using the Aarhus University shooting as a steppingstone, we discuss the pitfalls of lone-actor violence typologies and the advantages of the unifying lone-actor grievance-fueled violence conceptualization for both academia and practice.